2020
DOI: 10.1159/000506238
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Staging-Specific Differences in Recurrence-Free, Progression-Free, and Cancer-Specific Survival for Patients with T1 Bladder Cancer: A Systematic Review and Meta-Analysis

Abstract: Introduction: The efficiency of the T1 sub-staging system on categorizing bladder cancer (BC) patients into subgroups with different clinical outcomes was unclear. We summarized relevant evidences, including recurrence-free survival (RFS), progression-free survival (PFS), and cancer-specific survival (CSS), to analyze the prognostic significance of T1 sub-stage. Methods: Systematic literature searches of MED-LINE, EMBASE, and the Cochrane Library were performed. We pooled data on recurrence, progression, and C… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Also, MM invasion has been shown to be highly predictive of microinvasive UBC behavior [12]. Supporting this, a recent meta-analysis by Chen et al [13] confirms that T1 substaging based on MM invasion (T1a vs. T1b–c) is a significant prognostic factor of recurrence, progression-free survival, and cancer-specific survival. However, several series have failed to confirm pT1 substage as a reliable prognostic factor, leading to the view that the appropriate use of the T1 substaging system has yet to be determined.…”
Section: Discussion/conclusionmentioning
confidence: 87%
“…Also, MM invasion has been shown to be highly predictive of microinvasive UBC behavior [12]. Supporting this, a recent meta-analysis by Chen et al [13] confirms that T1 substaging based on MM invasion (T1a vs. T1b–c) is a significant prognostic factor of recurrence, progression-free survival, and cancer-specific survival. However, several series have failed to confirm pT1 substage as a reliable prognostic factor, leading to the view that the appropriate use of the T1 substaging system has yet to be determined.…”
Section: Discussion/conclusionmentioning
confidence: 87%
“…However, this so-called “radical transurethral resection” has been abandoned since then, having been shown to result in poorer oncological outcomes than trimodal therapy or radical cystectomy [2, 3]. In the setting of bladder-preserving therapeutic strategies for MIBC, the completeness of TURBT has largely been evidenced as the strongest predictor of long-term CSS suggesting the crucial role of maximal TURBT from an oncological standpoint [5, 18, 19]. Our report indicates that patients undergoing subsequent radical cystectomy may draw the same oncological benefits from an extensive transurethral resection.…”
Section: Discussionmentioning
confidence: 99%
“…With a projection of 16,390 deaths in 2017 in the US [1], it is also one of the deadliest malignancies. Transurethral resection of bladder tumors (TURBTs) is the mainstay of diagnosis for all bladder tumors [2, 3], and its therapeutic value for non-muscle-invasive bladder cancer (NMIBC) has been patently evidenced for decades although sub-staging T1 could be discussed [2-5]. The utmost importance of TURBT as part of bladder-sparing management in patients with muscle-invasive bladder cancer (MIBC) is also well established [6].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been reported to assess the depth and extent of tumor invasion into the lamina propria. Using the distinction between pT1a and pT1b based on invasion depth into muscularis mucosae, Chen et al [17] demonstrated that pT1b patients have worse RFS, PFS, and CSS compared to their counterparts. A second classification system, named metric substage, is based on invasion diameter and differentiates microinvasive (single spot < 0.5 mm) from extensive (≥0.5 mm) tumors.…”
Section: Evidence Synthesismentioning
confidence: 99%